Immunogenicity and reactogenicity of heterologous prime-boost vaccination with inactivated COVID-19 and ChAdOx1 nCoV-19 (AZD1222) vaccines, a quasi-experimental study - Kriangkrai Tawinprai; Pawornrath Jungsomsri; Onnicha Pinijnai; Fahsiri Tavonvunchai; Anchisa Lievjaroen; Paphada Suwannaroj; Taweegrit Siripongboonsitti; Thachanun Porntharukchareon; Gaidganok Sornsamdang; Teerapat Ungtrakul (Taylor & Francis Group, 2023)
The global supply of COVID-19 vaccines has been limited, and concerns have arisen about vaccine supply chain disruptions in developing countries. Heterologous prime-boost vaccination, which involves using different vaccines for the first and second doses, has been proposed to enhance the immune response. We aimed to compare the immunogenicity and safety of a heterologous prime-boost vaccination using an inactivated COVID-19 vaccine and AZD1222 vaccine with that of a homologous vaccination using AZD1222. This pilot involved 164 healthy volunteers without prior SARS-CoV-2 infection aged 18 years or older assigned to receive either the heterologous or homologous vaccination. The results showed that the heterologous approach was safe and well-tolerated, although the reactogenicity of the heterologous approach was higher. At 4 weeks after receiving the booster dose, the heterologous approach elicited a non-inferior immune response compared to the homologous approach in neutralizing antibody and cell-mediated immune response. The percentage of inhibition was 83.88 (79.72-88.03) in the heterologous and 79.88 (75.50-84.25) in the homologous group, a mean difference of 4.60 (−1.67-10.88). The geometric mean of interferon-gamma was 1072.53 mIU/mL (799.29-1439.18) in the heterologous group and 867.67 mIU/mL (671.94-1120.40) in the homologous group, a GMR of 1.24 (0.82-1.85). However, the binding antibody test of the heterologous group was inferior to the homologous group. Our findings suggest that the use of heterologous prime-boost vaccination with different types of COVID-19 vaccines is a viable strategy, especially in settings where vaccine supply is limited or where vaccine distribution is challenging.